Market Valuation of Illiquid Debt and Implications for Conflicts Among Creditors - Bartolini, Leonardo (International Monetary Fund, 1990)
We develop a formula for the market value of debt when the borrower's repayment capacity varies stochastically, and shortfalls are rolled over. The value of a marginal dollar of nominal claim is an S-shaped function of the ratio of the repayment capacity to the amount of nominal debt. Shifts of this curve are examined in response to changes in the underlying parameters. The calculations bring out some conflicts of interest among lenders of differing degrees of seniority. Most surprisingly, junior creditors gain when the loan is rescheduled on terms more favorable to the debtor